CHARACTER EDUCATIONAL VALUE OF KALAMATA NOVEL BY NI MADE PURNAMA SARI AND ITS RELEVANCE FOR TEACHING LITERATURE IN HIGH SCHOOL - Izzatu Khoirina; Suyitno Suyitno; Retno Winarni (English Department FBS UNP, 2017)
AbstractThe study states the research question on character educational value of Kalamata novel by Ni Made Purnama Sari and its relevance by learning literature in high school. The research objective is to describe and analyze the character educational value of Kalamata novel by Ni Made Purnama Sari and its relevancy by learning literature in high school. The used research method is descriptive qualitative. This study investigates 12 character educational values of Kalamata novel that consist of (1) social care, (2) religious, (3) creative, (4) environmental awareness, (5) friendly or communicative, (6) curiosity, (7) honest, (8) nationalism, (9) work hard, (10) tolerance, (11) achievement appreciation, and (12) nationality spirit. Those found character educational values is relevant with learning literature based on Indonesian teachers’ interview and 2013 Curriculum syllabus.Key words/phrases: character educational value, Kalamata novel, literature learning, literature learning relevancy NILAI PENDIDIKAN KARAKTER NOVEL KALAMATA KARYA NI MADE PURNAMA SARI DAN RELEVANSINYA UNTUK PEMBELAJARAN SASTRA DI SMAAbstrakPenelitian ini memuat rumusan masalah mengenai nilai pendidikan karakter novel Kalamata karya Ni Made Purnama Sari dan relevansinya dengan pembelajaran sastra di SMA. Tujuan penelitian ini adalah mendeskripsikan dan menganalisis nilai pendidikan karakter novel Kalamata karya Ni Made Purnama Sari dan relevansinya dengan pembelajaran sastra di SMA. Metode penelitian yang digunakan adalah metode kualitatif yang bersifat deskriptif. Penelitian ini menemukan 12 nilai pendidikan karakter pada novel Kalamata yang meliputi (1) peduli sosial, (2) religius, (3) kreatif, (4) peduli lingkungan, (5) bersahabat/komunikatif, (6) rasa ingin tahu, (7) jujur, (8) cinta tanah air, (9) kerja keras, (10) toleransi, (11) menghargai prestasi, dan (12) semangat kebangsaan. Nilai pendidikan karakter yang ditemukan sejumlah 12 butir tersebut relevan dengan pembelajaran sastra berdasarkan wawancara dua guru bahasa Indonesia dan silabus Kurikulum 2013.Kata Kunci/frase: nilai pendidikan karakter, novel Kalamata, pembelajaran sastra, relevansi pembelajaran sastra